The Mongolian People's Republic : toward a market economy - Milne, Elizabeth (Washington, D.C. : International Monetary Fund, 1991)
This paper reviews Mongolian's political and economic history, highlighting its changing economic structure following World War 11 and its recent efforts to introduce market mechanism.
"April 1991."
aia 23/11/17
Loans
Keywords: Mixed economy; Mongolia; Mongolia